LATE VISEAN LYGINOPTERIDOPHYTES FROM THE VICINITY OF THE TOWN OF BOROVICHI (NOVGOROD REGION): 1. CALAMOPITYALES - Orlova O.A.; Snigirevsky S.M. (My University, 2003)
Six species of Calamopityales (Lyginopteridophyta) are reported for the first time from the Upper Viscan sandy-silty deposits of Central Russia (vicinity of the town of Borovichi). Among these species, Sphenopteridium jurinae O. Orlova et S. Snigirevsky is a newly described one. The taxonomic composition and terminology describing pinnately compound leaves are discussed.
Keywords: Upper Visean; Paleozoic::Carboniferous::Mississippian::Middle::Visean; Палеозой::Каменноугольная::Средний::Визейский